Human Rights and the Environment – Theoretical, Moral and Religious Foundations - Đukić, Dalibor; Kisić, Rade (Human Rights and Environmental Protection from a Central and Eastern European Perspective, 2026)
This book chapter deals with the theoretical, moral, and religious foundations of environmental protection. One of the most significant developments in the legal protection of the environment is the growing demand for recognising the right to an environment of a certain quality as a universal human right. The chapter analyses theoretical approaches that establish a connection between environment and human rights. Furthermore, it examines the right to environment as an ethical demand that meets conditions to qualify as the basis of a human right. The chapter argues that the approach advocating for the recognition of a standalone substantive right to an environment of particular quality has gained prominence and is likely to lead to its recognition as a universal human right. This perspective does not preclude other theoretical approaches, which should be regarded as complementary. Nevertheless, this emerging right requires further theoretical development grounded in contemporary human rights theories.